Role of thoracentesis in the management of tuberculous pleural effusion - Mohammed A. Agha; Mahmoud M. El-Habashy; Mohamed A. Helwa; Rehab M. Habib (Egyptian Journal of Chest Disease and Tuberculosis, 2015)
Background: Tuberculous pleural effusion (TPE) is the second most common form of extrapulmonary tuberculosis (EPTB). Up to 50% after treatment complicated with pleural thickening. Pleural biopsy has been considered the gold standard in diagnosis of TPE but it is invasive, so that pleural fluid markers of TPE have been extensively evaluated as an alternative to pleural biopsy. Thoracentesis for measuring these fluid markers is important. Aim: Assessing the value of diagnostic thoracentesis (by measuring pleural adenosine deaminase levels) and role of therapeutic thoracentesis in preventing pleural thickening. Subjects and methods: 10 cases with transudative pleural effusion and 45 cases with already diagnosed exudative effusion (30 cases of TPE, and 15 cases of Malignant PE) were included. 50 ml pleural fluid samples were aspirated and sent for measuring ADA levels. The 30 cases of TPE were classified into 2 equal groups the 1st group started 6 months anti tuberculous therapy plus repeated thoracentesis while the 2nd started anti tuberculous therapy only. Chest CT scan was done after 2 and 6 months for assessment of pleural effusion and pleural thickening. Results: Patients with tuberculous pleural effusion had higher pleural effusion ADA levels (mean ± SD 68.51 ± 24.06) than those with malignant pleural effusion (mean ± SD 25.47 ± 12.09) or transudative pleural effusion (mean ± SD 16.58 ± 2.93) and these levels had highly a significant difference (P-value <0.001). Also, there was a significant difference (P-value <0.05) between levels of ADA in malignant and transudative pleural effusion. Using a cut-off point of the pleural fluid ADA (30.49 IU/L) with AUC of 96.7 (sensitivity 96.7%, specificity 84%, NPV 88%, PPV 95% and accuracy 91%) discrimination between tuberculous and other causes of pleural effusion occurred. Regarding the pleural thickening, after 2 months of ttt, in group I, 3 cases developed pleural thickening, while in group II, 9 cases developed thickening. After 6 months, there was one case of pleural thickening in group I, while in group II, 5 cases developed pleural thickening. And there was a significant difference (P value <0.05) between both groups, after 2 and 6 months of treatment. Conclusions: Thoracentesis is very important in the diagnosis of TPE either through diagnostic thoracentesis by measuring fluid markers such as ADA or therapeutic thoracentesis which is not only important for relieving dyspnea but also in preventing occurrence of pleural thickening that complicated cases of TPE.